2017
DOI: 10.1007/s12328-017-0775-7
|View full text |Cite
|
Sign up to set email alerts
|

A case of a mucin-producing bile duct tumor diagnosed over the course of 6 years

Abstract: We report a case of a mucin-producing intraductal papillary neoplasm of the intrahepatic bile duct (M-IPNB) diagnosed over a period of 6 years. A 64-year-old man underwent follow-up evaluations for an abdominal aortic aneurysm at our hospital. In 2009, a computed tomography (CT) scan revealed a simple hepatic cyst in segment 3 of the liver. Annual CT scans initially showed almost no change in the size or shape of the cyst. The cystic lesion, which measured 5 cm in 2014, had increased to 11 cm by 2015, and a so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…We searched the English-language literature published after 2010 for IPNBs developed from cystic hepatic tumors that were followed up for more than one year before treatment. Five cases, including the present case, were treated by surgical resection (Table 1)[9,22-24]. The follow-up period ranged from 2.5 to 13 years, and 4 patients showed gradual enlargement of the cystic tumor, initially without any clinical symptoms.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…We searched the English-language literature published after 2010 for IPNBs developed from cystic hepatic tumors that were followed up for more than one year before treatment. Five cases, including the present case, were treated by surgical resection (Table 1)[9,22-24]. The follow-up period ranged from 2.5 to 13 years, and 4 patients showed gradual enlargement of the cystic tumor, initially without any clinical symptoms.…”
Section: Discussionmentioning
confidence: 94%
“…Intrahepatic IPNB is characterized into 3 types: Ductectatic-type, cystic-type, and diffuse-type neoplasms[7,8]. Cystic-type IPNB often shares similar imaging features with cystic hepatic tumors, which may be misdiagnosed as mucinous cystic neoplasms, complicated hepatic cysts, cystic hemangiomas, lymphangiomas, hepatic foregut cysts, mesenchymal hematomas or teratomas[9-11]. Thus, careful follow-up and appropriate inspection of cystic hepatic tumors are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there are few reports about the natural course of type 1 IPNBs. Yamada et al reported that they performed surgery after observing a mucinproducing IPNB, for 6 years (10). With regard to the prognosis, type 1 IPNBs have markedly better prognoses than type 2 IPNBs.…”
Section: Discussionmentioning
confidence: 99%